Myelodysplastic Syndrome with Transfusion Dependence Treated with Venetoclax - Waqas Jehangir; Alexander Karabachev; Taimoor Jahangir; Elvira Umyarova (Case Reports in Hematology)
Myelodysplastic syndromes are characterized by ineffective hematopoiesis in one or more lineages of the bone marrow. They are a group of heterogeneous clonal stem cell malignancies with a high risk to progress to acute myeloid leukemia. Currently, there are no curative FDA-approved medications for myelodysplastic syndromes. Hematopoietic cell transplantation is potentially the only curative option; however, treatment is often unavailable due to age and comorbidities. Hypomethylating agents, azacitidine and decitabine, and the immunomodulatory agent, lenalidomide, are the only FDA approved medications for the treatment of MDS, all of which are noncurative. Venetoclax, an inhibitor of the antiapoptotic protein BCL-2 used to treat chronic lymphocytic leukemia, is currently being evaluated in clinical trials as a monotherapy in high-risk myelodysplastic syndromes/acute myeloid leukemia. We present a patient with transfusion-dependent myelodysplastic syndromes refractory to the current standard of care treatment not a candidate for hematopoietic cell transplantation who responded well to monotherapy treatment with venetoclax and has since remained transfusion-independent.